Rethinking Moses Òkè on the Recolonisation Project - David A. Oyedola (The Thinker)
The study engages Òkè’s submission that a people that continually looks back to its past that failed then, and could not sustain them for present salvation, must change their perception and attitude to that past or hold themselves ready for eventual recolonisation. It presents concise discussions on Òkè’s recolonisation project (RP) – both for and against. It argues that Òkè and the commentators alike, i.e. the defenders and the critics, have failed to pay attention to the fact that Òkè’s RP does not presuppose a complete mockery of decolonisation campaign. Nevertheless, Òkè can be seen in the light of his consistency in maintaining the same fundamental principles that made him to reject decolonisation, and propose recolonisation as the alternative. This made Òkè to concede that recolonisation is possible. The study employs the methods of conceptual analysis and philosophical argumentation.